Lasioglossin-III : antimicrobial characterization and feasibility study for immobilization applications - Mishra, Biswajit (2013)
Prevalent bacterial colonization and subsequent biofilm formation in biomedical implants demand for improved antimicrobial properties of these devices. To address this problem, immobilizing antimicrobial peptides (AMPs) on implants is a promising solution because of their biocompatibility and lesser likelihood to incur pathogen resistance. This study presents a systematic approach towards evaluating the feasibility of Lasioglossin-III (Lasio-III) (a new bee venom AMP, found in Lasioglossum laticeps) to be tethered onto biodevices. Antimicrobial characterization of Lasio-III in solution confirms the peptide’s membranolytic mode of action and its salt-resistant, broad antimicrobial spectrum activity and anti-biofilm properties against Gram negative and Gram positive bacteria. Lassio-III was covalently immobilized on silicon surfaces using APTES and PEG spacers of varying lengths. Surface characterization of the AMP-immobilized silicon was done using water contact angle measurements, XPS analysis and ellipsometry. Even at modest surface peptide concentrations of y180 ng cm22 , Lassio-III showed antibacterial activities which were further enhanced with increasing PEG spacer lengths, as determined by live CFU counting and ATP leakage experiments. This proof-of-concept study demonstrates the potential of Lasio-III as an antimicrobial coating candidate.